Classical texts in the art treatises of early Modern Period - Riklius, Tomas (Literatūra, 2019)
This paper discusses the quotation frequency and reference strategies of Leon Battista Alberti, Federico Borromeo, and Gabriele Paleotti. These three Catholic art theoreticians of Early Modern period engaged Classical texts as the point of reference and expertly manipulated the Classical sources to provide contextual arguments in the formation of their own artistic theories. Alberti, Borromeo, and Paleotti directly alluded or referred to Pliny the Elder, Plutarch, Xenophon, Strabo, Aulus Gellius, and other Classical sources rather extensively. This can be noticed from various quotation strategies applied in Alberti, Borromeo, and Paleotti treatises and by statistical data on quotation frequency in Alberti’s De pictura, Paleotti’s Discorso intorno alle immagini sacre e profane, and Borromeo’s De pictura sacra.
Keywords: Leon Battista Alberti; Federico Borromeo; Gabriele Paleotti; art theory; art treatises; humanist education; early modern period